Presentation - Social and Family Management of Health Problems - Aubry, François; Audy, Émilie (Enfances, Familles, Générations)

(untitled) (INRS-UCS, 2017)
This presentation of the issue on "Family Management of Health Problems" examines the roles of family members, particularly women, in caring or assisting a relative facing a health problem. It also introduces the eight thematic articles.